Early-Onset Parkinson Disease Screening in Patients From Nigeria - Milanowski, Lukasz M.; Oshinaike, Olajumoke; Broadway, Benjamin J.; Lindemann, Jennifer A.; Soto-Beasley, Alexandra I.; Walton, Ronald L.; Hanna Al-Shaikh, Rana; Strongosky, Audrey J.; Fiesel, Fabienne C.; Ross, Owen A.; Springer, Wolfdieter; Ogun, Shamsideen Abayomi; et al. (Frontiers in Neurology, 2021)
Nigeria is one of the most populated countries in the world; however, there is a scarcity of studies in patients with age-related neurodegenerative diseases, such as Parkinson disease (PD). The aim of this study was to screen patients with PD including a small cohort of early onset PD (EOPD) cases from Nigeria for PRKN, PINK1, DJ1, SNCA multiplication, and LRRK2 p.G2019S. We assembled a cohort of 109 Nigerian patients with PD from the 4 main Nigerian tribes: Yoruba, Igbo, Edo, and Hausa. Fifteen cases had EOPD (defined as age-at-onset <50 years). All patients with EOPD were sequenced for the coding regions of PRKN, PINK1, and DJ1. Exon dosage analysis was performed with a multiplex ligation-dependent probe amplification assay, which also included a SNCA probe and LRRK2 p.G2019S. We screened for LRRK2 p.G2019S in the entire PD cohort using a genotyping assay. In 15 patients with EOPD, 22 variants were observed (PRKN, 9 [40.9%]; PINK1, 10 [45.5%]; and DJ1, 3 [13.6%]). Three (13.6%) rare, nonsynonymous variants were identified, but no homozygous or compound heterozygous carriers were found. No exonic rearrangements were present in the 3 genes, and no carriers of SNCA genomic multiplications or LRRK2 p.G2019S were identified. The PINK1 p.R501Q functional analysis revealed pathogenic loss of function. More studies on age-related neurodegenerative diseases are needed in sub-Saharan African countries, including Nigeria. Population-specific variation may provide insight into the genes involved in PD in the local population, but may also contribute to larger studies performed in White and Asian populations.